Comparison of mixed refrigerant cycles for natural gas liquefaction: From single mixed refrigerant to mixed fluid cascade processes. (1st June 2023) - Tak, Kyungjae; Park, Jaedeuk; Moon, Il; Lee, Ung
Abstract: Natural gas liquefaction plants have adopted mixed refrigerant (MR) cascade configurations to improve energy efficiency and process irreversibility. The MR cascade processes consist of multi-stream heat exchangers (MSHEs) and compression systems for each MR cycle. In this study, MR cascade cycles were modeled and optimized to compare and analyze the MR cascade processes. Compared to a single MR process with one MSHE, considered as the base case herein (995.0 kJ/kg LNG), a triple MR process showed 19.0% energy reduction (805.6 kJ/kg LNG). Because triple MR processes require at least three MSHEs, a single MR process with three MSHEs was also compared, which obtained only 3.9% energy reduction (956.1 kJ/kg LNG) compared to the base case. Additional process configurations, such as MR cascades with two MSHEs per MR cycle and dual MR processes, were also considered in this study. An exergy analysis of the optimized energy results revealed that the decreased exergy loss in the heat exchangers was the main factor for the energy reductions. For example, a specific work reduction of 129.5 kJ/kg LNG among 189.4 kJ/kg LNG for the triple MR process was attributed to the exergy improvement at the MSHEs and coolers. Graphical abstract: Image 1 Highlights: Mixed refrigerant cycles to liquefy natural gas optimized. Single, dual, and triple mixed refrigerant cycles compared. Single cycle with 1, 2, and 3 multistream heat exchangers investigated. Energy requirement of 995 kJ/kg LNG in base case. Energy savings of 19% (806 kJ/kg LNG) for triple cycles from base case.